The Role of Social Interaction Patterns in Character Formation and Community Awareness in the School Environment - indo123, The Role of Social Interaction Patterns; Ilham Arifin; Didik Tri Setyoko (International Journal of Asian Education, 2025)
Character education in schools faces challenges related to social interaction patterns that influence students' moral development in the digital era. This study aims to examine the role of social interaction patterns in character formation and community awareness through a qualitative literature review. The population included scientific literature from 2021 to 2025 from journals, books, and national laws; a sample of 20-30 sources was selected through purposive sampling based on thematic relevance. Instruments, consisting of scientific documents, were analyzed through systematic collection in Google Scholar, thematic data reduction (positive-negative interactions), and literature triangulation. The results show that positive interactions such as cooperation and effective communication foster discipline, empathy, and tolerance, while negative interactions such as bullying hinder moral development. The conclusions emphasize the need for an inclusive environment through school-family collaboration for a responsible generation, with limitations in secondary data.